Parallel Processing and Applied Mathematics 13th International Conference, PPAM 2019, Bialystok, Poland, September 8-11, 2019, Revised Selected Papers, Part I - Wyrzykowski, Roman; Deelman, Ewa.; Dongarra, Jack.; Karczewski, Konrad; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
Chapters "Parallel Adaptive Cross Approximation for the Multi-trace Formulation of Scattering Problems" and "A High-Order Discontinuous Galerkin Solver with Dynamic Adaptive Mesh Refinement to Simulate Cloud Formation Processes" are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Numerical Algorithms and Parallel Scientific Computing -- Emerging HPC Architectures -- Performance Analysis and Scheduling in HPC Systems -- Environments and Frameworks for Parallel/Distributed/Cloud Computing -- Applications of Parallel Computing -- Parallel Non-numerical Algorithms -- Soft Computing with Applications -- Special Session on GPU Computing -- Special Session on Parallel Matrix Factorizations.
Keywords: Software engineering; Computer engineering; 9; Computer input-output equipment; Logic design; Computer science -- Mathematics; Computer programming; Software Engineering; Computer Engineering and Networks; Input/Output and Data Communications; Logic Design; Mathematics of Computing; Programming Techniques